The determinants that influence customers’ preference on selecting local commercial banks in Malaysia - Lew, Jun Xuan; Mah, Hin Kit; Tan, Jing Ven; Lee, Jia Mei; Cheng, Yee Lay (2019)
The purpose of this research is to determine the relationship between customers’ preference on selecting local commercial banks with its determinants in Malaysia.This study is designed to achieve the following objectives: (1) To determine the relationship between service quality and customers’ preference on selecting local commercial banks in Malaysia.(2) To determine the relationship between technological factor and customers’ preference on selecting local commercial banks in Malaysia.(3) To determine the relationship between convenience factor and customers’ preference on selecting local commercial banks in Malaysia.(4) To determine the relationship between corporate image of bank and customers’ preference on selecting local commercial banks in Malaysia. (5) To determine the relationship between marketing and advertising of bank and customers’ preference on selecting local commercial banks in Malaysia.(6) To determine the relationship between core banking services and customers’ preference on selecting local commercial banks in Malaysia.This research paper is helpful for banking industry, marketing managers, policy makers and researchers in the future. In this research, data are collected from primary sourcesthrough distributing questionnaire to respondents while the target population is Malaysian who currently owned an account or used the services provided by the local commercial banks. A total of 350 sets of questionnaires are used by extracting out the data and Statistical Package for Social Science (SPSS) version 20.0 was used to analyze the data which collected from the survey. Respondent's feedback was analyzed through Reliability Test, Pearson Correlation Coefficient Analysis, and Multiple Linear Regression Analysis. The results generated from SPSS shows that all of the six independent variables which are service quality, technological factor, convenience factor, corporate image of bank, marketing and advertising of bank, and core banking services have significant positive relationship with the dependent variable.